Analisis Risiko Produksi Peternakan Ayam Broiler Di Kecamatan Sukowono Kabupaten Jember - Maryam Haniifah; Syamsul Hadi Kusuma; Henik Prayuginingsih (STIE Mandala Jember, 2021)
The study was conducted to examine the problemsed of broiler chicken farms at Sukowono District, Jember Regency. The research objectives are; (1) Identifying sources of production risk, (2) Knowing the opportunities for production risk, (3) Knowing the impact of production risk, (4) Formulate risk status and alternative strategies applied to overcome production risks. This type of research is descriptive and survey methods, using primary and secondary data with the location of the study chosen deliberately (purposive). Sampling uses the Total Sampling method. Data analysis using z-score, Value at Risk (VaR), risk status and risk map. Based on the results of the study, it could be concluded that; (1) Sources of production risk are diseases, rejected chickens, environmental disturbances and predatory pests, (2) Opportunities for production risk are environmental disorders of 62,17%, reject chicken 59,87%, pests and predators 57,14%, and diseases 44,04%, (3) The impact of the risk in the form of potential losses originating from the disease amounted to IDR 9.303.171, environmental disturbances amounting to IDR 6.814.817, reject chicken amounting to IDR 6.684.948 and pests and predators of IDR 264.718 of 109.000 chickens, (4) Risk status for sources of risk of reject chicken and environmental disturbances is severe, for sources of risk of predatory diseases and pests are moderate. The results of risk mapping indicate that there are preventive and mitigation strategies. Environmental disorders and reject chicken are a source of risk that has a great opportunity and impact. Keywords: Broiler chicken, Risk mapping, Production risk, Risk source.